Imperial Panegyric from Diocletian to Honorius, red. Adrastos Omissi, Alan J Ross, Liverpool University Press, Translated Texts for Historians, Contexts 3, Liverpool 2020, ss. 296 + XI - Szopa, Adrian (Vox Patrum, 2022)
Rewiev of the book Imperial Panegyric from Diocletian to Honorius, ed. by Adrastos Omissi and Alan J Ross, Liverpool University Press, Translated Texts for Historians, Contexts 3, Liverpool 2020, pp. 296 + XI.